Survival rates in the world's southernmost forest bird community - Sandvig, Erik M.; Quilodran, Claudio S.; Altamirano, Tomas A.; Aguirre, Francisco; Barroso, Omar; de Aguilar, Juan Rivero; Schaub, Michael; Kery, Marc; Vasquez, Rodrigo A.; Rozzi Marin, Ricardo Roberto (My University, 2023)
The Magellanic sub-Antarctic Forest is home to the world's southernmost avian community and is the only Southern Hemisphere analogue to Northern Hemisphere temperate forests at this latitude. This region is considered among the few remaining pristine areas of the world, and shifts in environmental conditions are predominantly driven by climate variability. Thus, understanding climate-driven demographic processes is critical for addressing conservation issues in this system under future climate change scenarios. Here, we describe annual survival patterns and their association with climate variables using a 20-year mark-recapture data set of five forest bird species in the Cape Horn Biosphere Reserve. We develop a multispecies hierarchical survival model to jointly explore age-dependent survival probabilities at the community and species levels in a group of five forest passerines. At the community level, we assess the association of migratory behavior and body size with survival, and at the species level, we investigate the influence of local and regional climatic variables on temporal variations of survival. We found a positive effect of precipitation and a negative effect of El Nino Southern Oscillation on juvenile survival in the white-crested Elaenia and a consistent but uncertain negative effect of temperature on survival in juveniles and 80% of adults. We found only a weak association of climate variables with survival across species in the community and no temporal trends in survival for any of the species in either age class, highlighting apparent stability in these high austral latitude forests. Finally, our findings provide an important resource of survival probabilities, a necessary input for assessing potential impacts of global climate change in this unique region of the world.
Keywords: capture-mark-recapture; climate change; forest birds; hierarchical model; multispecies cjs model; patagonia; survival